(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
This article analyses the concepts of "legal idealism" and "legal nihilism". Their cultural and historical basis is considered. The answer to the question of how to limit these sociolegal phenomena in modern conditions is sought. The author concludes that overcoming legal nihilism is a very long and complex process. The main ways to overcome legal nihilism are popularization of legal awareness; increasing the level of public culture (not only general, but also legal); improvement of existing legislation; prevention of offences; legal education; mass legal education; strengthening state discipline, law norms and legality; ensuring freedoms and human rights; respect for personality; legal reforms; training of highly qualified lawyers, etc.